Towards a Reading of Wordsworth’s “Now ye meet in the cave” - Hugues, John (Romanticism on the Net)

(untitled) (Université de Montréal, 2018)
Wordsworth’s very early “Now ye meet in the cave” (dating from 1786 or a little later) is a strange fragment. It emanates from a desperate, unidentified speaker and bears on the burial of a mysterious female whose death is yet uncertain. It has been largely passed over by critics, with the exception of Duncan Wu—who suggested the poem might be about Wordsworth’s mother. This article follows this intuition, and explores common features of language and theme with a range of works of Wordsworth’s early youth. The conclusion is that “Now ye meet in the cave” is a significant document, and expresses fundamental, yet inevitably covert, facets of Wordsworth’s sensibility. In broadening this case, the article relates a final close reading of the poem to two important, inter-related contexts. The first is Stanley Cavell’s discussion of Romantic scepticism as a metaphysical fantasy involving the refusal of finitude, and a suspended sense of the world’s existence. The second references recent research in child psychology that demonstrates the automatic unconscious fantasy of a young orphaned child who affectively bargains his knowledge of his parent’s death for the belief that she still somehow is incorporated, within himself, and